Overview of the Problems of Equivalence in Translating Texts - Hamroyeva Sharifa (Periodica Journal, 2024)
Equivalence in translation is a fundamental concept that lies at the heart of the translator's craft. It refers to the process of accurately conveying the meaning, style and tone of the source text in the target language while taking into account various linguistic and cultural differences. Achieving equivalence in translation involves striking a delicate balance between fidelity to the original text and readability, naturalness in the target language. Therefore, this paper investigates the types of equivalency and the views of scholars about the issues in finding the appropriate equivalent words as well as their importance in translation
Keywords: Equivalent; Source Text; Formal Equivalency; Dynamic Equivalency